Opportunities for second language learning in online search sequences during a computer-mediated tutoring session. Issue 2 (3rd April 2022) - Nguyen, Hanh thi; Choe, Ann Tai; Vicentini, Cristiane
ABSTRACT: To inform pedagogical decisions about using technology, it is important to understand from the ground up how technology is utilised during language learning activities. This paper takes an ethnomethodological conversation analytic approach to examine a learner's participation in epistemic management actions and its consequences for second language learning during online search sequences. Data come from a conversation-for-learning between a tutor and a tutee conducted via voice and text chat in Skype. Microanalysis of the online search sequences reveals that the emergence of a teachable/learnable can be spurred by the confluence of interactional practices and computer technology affordances. Further, we show how technological friction can induce rather than constrain language use and practice. Our findings call for more attention to coordinated online searches as a learning activity in its own right.